Carotenoid status in type 2 diabetes patients with and without retinopathy. Issue 10 (30th April 2021) - Shalini, T.; Jose, Sarin S.; Prasanthi, P. S.; Balakrishna, N.; Viswanath, K.; Reddy, G. Bhanuprakash
Abstract : This study reports a decrease in plasma carotenoid levels in diabetes patients with retinopathy (DR) compared to diabetes patients without retinopathy (NDR) and control subjects. Abstract : Diabetic retinopathy (DR) is one of the leading causes of blindness. Carotenoids are plant-derived pigments required for general health and particularly for vision. In this study, we evaluated the dietary intake and blood carotenoid levels of type 2 diabetes (T2D) patients with and without DR. A cross-sectional case–control study was conducted among 151 age-matched controls and 344 T2D patients, of which 194 had DR and 150 had no DR (NDR). After a complete ophthalmic examination, the demographic, anthropometric and clinical profiles were obtained. Carotenoids in the plasma were measured by HPLC and dietary intakes were obtained using a food frequency questionnaire. The mean plasma levels of carotenoids (except γ-carotene) were significantly lower in the DR group compared to the Control and NDR groups. The dietary intakes of zeaxanthin, lycopene, α-carotene and β-carotene were significantly lower in the NDR group compared to the Control group, and were further lower in the DR group compared to the NDR group. Plasma carotenoid levels were significantly inversely associated with the duration of diabetes, RBS and HbA1c but positively associated with HDL. This study demonstrated decreased plasma levels and lower dietary intakes of carotenoids in DR subjects.